Promotion of Information Reception Readiness for Ineffective Health Management in The Community with Hypertension - Dwiyanti, Faradilah Mulya; Ati, Niken Asih Laras; Susumaningrum, Latifa Aini; Ardhani, Ni Ketut (Jurnal Kesehatan Komunitas Indonesia, 2025)
Introduction: Hypertension is a cardiovascular disease in the heart and blood vessels and a serious health problem worldwide. This condition can be characterized by systolic blood pressure ≥ 140 mmHg and diastolic blood pressure ≥ 90 mmHg. An unhealthy lifestyle and a deficit of information account for most of the elements that cause hypertension, and problems arise with ineffective health management. Objective: This study aims to determine the description of community nursing care with Ineffective Health Management: Hypertension in the community of neighborhood 03 in Jumerto Village. Method: This study uses descriptive analysis with a total sampling of 33 samples. Data were collected using a DASH questionnaire, which was carried out before and after the intervention. Data analysis used the Wilcoxon test, with the research results showing a p-value. Result: The results of the intervention showed that there was a significant difference in systolic and diastolic blood pressure before and after the intervention with a significance level (p-value< 0.05), and there is an increase in health education about the hypertension diet with a p-value of 0.000 (p value< 0.05). Conclusion: Health education interventions and demonstrations of giving bay leaf decoction drinks as non-pharmacological therapy can overcome the problem of ineffective health management nursing.